1990
DOI: 10.1111/j.1439-0418.1990.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of Labiatae for controlling honey bee varroosis

Abstract: The efficiency of Labiatae essential oils was compared with a classical aerosol treatment, including the acaricidic substance amitraz at the 0.25 concentration. The tested concentrations of the experimental mixture were 1 YO of thyme (Thymus vulgaris L.) and 0.5 YO of sage (Salvia oflicinalis L.). These products were also injected into each colony by the aerosol way for one minute. 4 applications in an interval of 3 or 4 days constitute the treatment. The dead mites (Varroajacobsoni Oud.) were counted everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Colin [18] compared an aerosol application of water emulsions of 1 % thyme oil (main ingredients p-cymene and thymol) and 0. Liebig [57] tested this product in brood-free colonies in November.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colin [18] compared an aerosol application of water emulsions of 1 % thyme oil (main ingredients p-cymene and thymol) and 0. Liebig [57] tested this product in brood-free colonies in November.…”
Section: Introductionmentioning
confidence: 99%
“…Liebig [57] tested this product in brood-free colonies in November. Four, 1-min treatments at intervals of 3-4 days with 100 mL of BIOLOGIC V® per 1.5 L deionized water were carried out, essentially as described by Colin [18]. Mite [52].…”
Section: Introductionmentioning
confidence: 99%
“…All essential oils caused mite mortality without severe harmful effects on adult bees. Colin, (1990) reported that essential oils of thyme, thymus vulgaris and sage, salvia officinalis effectively control V. jacobsoni. Gashout and Guzman-Novoa, (2009) evaluated some essential oils for their toxicity to the parasitic mite V. destructor.…”
Section: Essential Oils Against Honey Bee Mitesmentioning
confidence: 99%
“…Colin (1990) demonstrated that aerosol application of water emulsions of 1 % thyme oil and 0.5 % sage oil with 0.25 % Amitraz solution removed 99% of mites. However, mites have shown resistance to these low amitraz levels but not to higher levels (Corniffe, personal communication).…”
Section: Amitrazmentioning
confidence: 99%
“…However, Melathopoulos (2000) found that neem treatments caused a significant loss of queens and may be acutely toxic to immature bees. Both Colin (1990) and Melathopoulos (2000) found the oil to have a repellent effect on the bees and not useful as a sugar patty 1 additive. On the other hand, Allam et al (2003) and Liu (1995) consists of only field crops; however, farms of fruit trees border its fences with plant nurseries nearby.…”
Section: Neemmentioning
confidence: 99%